OPTIMIZATION OF GRANULOMETRIC COMPOSITION OF DRY FRIABLE SAND BLENDS - V. S. Doroshenko (Литьë и металлургия)
A method for optimizing the composition of the grain loose sand mixtures by placing the binder particles into the pores of the frame sand compaction of these mixtures. An example of calculation of grain composition of such a mixture.